Transatlantic spiritualism and nineteenth-century American literature - Bennett, Bridget (Palgrave Macmillan, 2007)
Why did so many Americans visit and write about, seances? What are the connections between the 'emergence' of spiritualism in 1848 and earlier kinds of supernatural phenomena? This book asks about the cultural and political meanings of spiritualism in the 19th century United States. In order to re-assess both transatlantic spiritualism and the culture in which it emerged, Bennett locates spiritualism within a highly technologized transatlantic capitalist culture. She argues that, through performances in which the dead speak through and to the living, white Americans' most profound anxieties about political and cultural dispossession, especially of Indians, are articulated.